2003
DOI: 10.1007/s00259-003-1198-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid normalization of osseous FDG uptake following traumatic or surgical fractures

Abstract: It is known that following a traumatic fracture or surgical intervention, bone scintigraphy reveals positive results for an extended period of time, posing a challenge when evaluating patients for possible malignancy or superimposed osteomyelitis. Previous reports indicate that acute fractures can also result in increased fluorine-18 fluorodeoxyglucose (FDG) accumulation and therefore cause difficulties when patients are evaluated for other indications by FDG-PET. The purpose of this study was to assess the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 13 publications
0
58
1
5
Order By: Relevance
“…In bone scintigraphy, increased uptake persists for many months after fracture and depends on the site of injury (90). Although the duration of abnormal 18F-FDG uptake in benign fractures is unknown, Zhuang et al (95) reported that 18F-FDG uptake rapidly decreased with time after fracture and that it should be normal within a maximum of 3 months. Shon and Fogelman (90) reported that the most intense 18F-FDG uptake was observed when MI by PET was performed 17 days after fracture, among the four-case series where imaging was performed from 17 days to 8 weeks.…”
Section: Differential Diagnosis Of Spinal Tumor By Petmentioning
confidence: 99%
“…In bone scintigraphy, increased uptake persists for many months after fracture and depends on the site of injury (90). Although the duration of abnormal 18F-FDG uptake in benign fractures is unknown, Zhuang et al (95) reported that 18F-FDG uptake rapidly decreased with time after fracture and that it should be normal within a maximum of 3 months. Shon and Fogelman (90) reported that the most intense 18F-FDG uptake was observed when MI by PET was performed 17 days after fracture, among the four-case series where imaging was performed from 17 days to 8 weeks.…”
Section: Differential Diagnosis Of Spinal Tumor By Petmentioning
confidence: 99%
“…Sin embargo, en los casos donde hay captación aumentada de FDG, no permite diferenciar entre ambas causas, debiendo utilizarse otro método de estudio para su diferenciación 34 . Entre las causas de falsos positivos para las infecciones óseas se encuentran artritis inflamatorias, fracturas, reparación ósea y cirugías recientes, ya que pueden presentarse como áreas focales de aumento del metabolismo 35 .…”
Section: Infecciones óSeasunclassified
“…Increased FDG accumulation in PET is also associated with inflammatory arthritis, fractures, normally healing bone and degenerative changes (14)(15)(16). However in contrast to bone scintigraphy, FDG PET rapidly normalizes after traumatic or surgical fractures (14,16) as fibroblast predominate in normally healing bone, and FDG uptake quickly subsides 4 months after surgery (17).…”
Section: Osteomyelitismentioning
confidence: 99%
“…However in contrast to bone scintigraphy, FDG PET rapidly normalizes after traumatic or surgical fractures (14,16) as fibroblast predominate in normally healing bone, and FDG uptake quickly subsides 4 months after surgery (17). The healing process shows most of the cells that are present in inflammation (18).…”
Section: Osteomyelitismentioning
confidence: 99%